Durable blockade of PD-1 signaling links preclinical efficacy of sintilimab to its clinical benefit. Issue 8 (17th November 2019) - Wang, Jie; Fei, Keke; Jing, Hua; Wu, Zhihai; Wu, Weiwei; Zhou, Shuaixiang; Ni, Haiqing; Chen, Bingliang; Xiong, Yan; Liu, Yanpeng; Peng, Bo; Yu, Dechao; et al.
ABSTRACT: Blockade of immune checkpoint pathways by programmed cell death protein 1 (PD-1) antibodies has demonstrated broad clinical efficacy against a variety of malignancies. Sintilimab, a highly selective, fully human monoclonal antibody (mAb), blocks the interaction of PD-1 and its ligands and has demonstrated clinical benefit in various clinical studies. Here, we evaluated the affinity of sintilimab to human PD-1 by surface plasmon resonance and mesoscale discovery and evaluated PD-1 receptor occupancy and anti-tumor efficacy of sintilimab in a humanized NOD/Shi-scid-IL2rgamma (null) (NOG) mouse model. We also assessed the receptor occupancy and immunogenicity of sintilimab from clinical studies in humans (9 patients with advanced solid tumor and 381 patients from 4 clinical studies, respectively). Sintilimab bound to human PD-1 with greater affinity than nivolumab (Opdivo®, MDX-1106) and pembrolizumab (Keytruda®, MK-3475). The high affinity of sintilimab is explained by its distinct structural binding mode to PD-1. The pharmacokinetic behavior of sintilimab did not show any significant differences compared to the other two anti-PD-1 mAbs. In the humanized NOG mouse model, sintilimab showed superior PD-1 occupancy on circulating T cells and a stronger anti-tumor effect against NCI-H292 tumors. The strong anti-tumor response correlated with increased interferon-γ-secreting, tumor-specific CD8+ T cells, but not with CD4+ Tregs in tumor tissue. Pharmacodynamics testing indicated a sustained mean occupancy of ≥95% of PD-1 molecules on circulating T cells in patients following sintilimab infusion, regardless of infusion dose. Sintilimab infusion was associated with 0.52% (2/381 patients) of anti-drug antibodies and 0.26% (1/381 patients) neutralizing antibodies. These data validate sintilimab as a novel, safe, and efficacious anti-PD-1 mAb for cancer immunotherapy.